2021
DOI: 10.37360/blacpma.21.20.5.37
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and insecticidal activity of Garcinia gardneriana (Planchon & Triana) Zappi (Clusiaceae) essential oil

Abstract: The present study aimed to analyze the chemical composition of the essential oil from Garcinia gardneriana (Planchon & Triana) Zappi leaves and fruits, and to determine its acaricidal activity on Rhipicephalus microplus by larval packet test and larvicidal action on Aedes aegypti by larval immersion test. The chemical analysis of the essential oil by gas chromatography-mass spectrometry identified sesquiterpene hydrocarbons and oxygenated sesquiterpenes in bacupari leaves and fruits, and α-cedrene, α-chami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…According to the literature, no studies on the identification of C. mildbraedii bark essential oil components have been published. The components of the essential oil were identified by comparing their MS patterns and retention index (RI) with those of known chemicals published in the literature [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. The chemical composition of the essential oil of C. mildbraedii bark was quantified using GC-FID and identified via GC-MS. Table 5 shows 30 compounds identified, representing 65% of all compounds detected in the GC-MS investigation of the essential oil, with 9 sesquiterpene hydrocarbons (26%), 7 oxygenated sesquiterpenes (22%) and 14 other compounds (17%).…”
Section: Resultsmentioning
confidence: 99%
“…According to the literature, no studies on the identification of C. mildbraedii bark essential oil components have been published. The components of the essential oil were identified by comparing their MS patterns and retention index (RI) with those of known chemicals published in the literature [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. The chemical composition of the essential oil of C. mildbraedii bark was quantified using GC-FID and identified via GC-MS. Table 5 shows 30 compounds identified, representing 65% of all compounds detected in the GC-MS investigation of the essential oil, with 9 sesquiterpene hydrocarbons (26%), 7 oxygenated sesquiterpenes (22%) and 14 other compounds (17%).…”
Section: Resultsmentioning
confidence: 99%
“…According to Fernandez et al [ 132 ] α- trans -bergamotene was the major component of the EO of the fruits of Garcinia gardneriana and showed toxicity against Aedes aegyptus mosquito larvae. Vinturelle et al [ 133 ] reported that the EO of Copaifera officinalis contained α- trans -bergamotene as one of the compounds with the highest content and caused 84.60% mortality in engorged females of the tick Rhipicephalus microplus.…”
Section: Resultsmentioning
confidence: 99%
“…This activity was also demonstrated by the volatiles from leaves and fruits of Garcinia gardneriana (Planch. & Triana) Zappi, a member of Clusiaceae family (Fernandez et al 2021). Secondly, the fruit latex, taking into account the larvicidal effects of β-caryophyllene and β-caryophyllene oxide (Senthil-Nathan 2020), which also reinforces a possible activity of the volatiles from C. fluminensis.…”
Section: An Acad Brasmentioning
confidence: 99%